Modulatory effect of prostaglandins on human monocyte activation for killing of high- and low-virulence strains of Paracoccidioides brasiliensis - Soares, AMVC; Calvi, Sueli Aparecida [UNESP]; Peracoli, MTS; Fernandez, A. C.; Dias-Melicio, Luciane Alarcão [UNESP]; Dos Anjos, A. R. (Blackwell Science, 2001)
The effect of indomethacin (Indo), a cyclo-oxygenase inhibitor, on the monocyte-mediated killing of a low-(Pb265) and a high-(Pb18) virulence strain of Paracoccidioides brasiliensis was examined. The Pb18 strain was not killed by either non-activated or interferon-gamma (IFN-gamma)-activated human monocytes but these cells did show fungicidal activity if pretreated with Indo. In contrast with IFN-gamma tumour necrosis factor-alpha (TNF-alpha) was very effective at stimulating the fungicidal activity of monocytes. While the low-virulence strain, Pb265, could not be killed by monocytes, cells preincubated with IFN-gamma demonstrated fungicidal activity. The killing of this strain was also induced by pretreatment of monocytes with Indo. The results suggest a negative role for prostaglandins, which are synthesized via the cyclo-oxygenase pathway, in the regulation of monocyte-mediated killing of virulent and avirulent strains of P. brasiliensis and that TNF-alpha generation during the fungus-monocyte interaction is more important in the killing of Pb265 than Pb18.